Diverse selection pressures shaping the genetic architecture of behçet disease susceptibility - Sezgin, Efe; Kaplan, Elif (Frontiers in Genetics, 2022)
Behçet disease (BD) is a polygenic, multifactorial, multisystem inflammatory condition with unknown etiology. Global distribution of BD is geographically structured highest prevalence is observed among East Asian, Middle Eastern, and Mediterranean populations. Although adaptive selection on a few BD susceptibility loci is speculated, a thorough evolutionary analysis on the genetic architecture of BD is lacking. We aimed to understand whether increased BD risk in certain human populations is due to past selection on BD associated genes and their derived variants in geographic regions where BD prevalence is high, and conducted comprehensive population genetic and genomic analyses primarily with East Asian (high BD prevalence), European (low/very low BD prevalence), and African (very low/no BD prevalence) populations. Comparison of ancestral and derived alleles’ frequencies versus their reported susceptible or protective effect on BD showed both derived and ancestral alleles are associated with increased BD risk. Contrary to expectations, variants showing higher risk to and more significant association with BD had smaller allele frequency differences and showed less population differentiation compared to variants that showed smaller risk and less significant association with BD indicating these alleles are not unique to East Asians but are also found in other world populations at appreciable frequencies, and argue against selection favoring these variants only in populations with high BD prevalence. BD associated gene analyses showed similar evolutionary histories driven by neutral processes for many genes or balancing selection for HLA genes in all three populations. However, nucleotide diversity in several HLA region genes was much higher in East Asians suggesting selection for high nucleotide and haplotype diversity in East Asians. Recent selective sweep for genes involved in pattern recognition, peptide processing, immune and cellular differentiation regulation was observed only in East Asians. In conclusion, the evolutionary processes shaping the genetic diversity in BD risk genes are diverse, and elucidating the underlying specific selection mechanisms is complex. Several of the genes examined in this study are risk factors for other inflammatory diseases. Thus, our conclusions are not only limited to BD but have broader implications for other inflammatory diseases.